2018
DOI: 10.1039/c8qm00343b
|View full text |Cite
|
Sign up to set email alerts
|

Amplified antimicrobial action of chlorhexidine encapsulated in PDAC-functionalized acrylate copolymer nanogel carriers

Abstract: We demonstrate a strong enhancement of the antimicrobial action of chlorhexidine which is attributed to the electrostatic adhesion of the cationic nanocarriers on the microbial cell walls which leads to their accumulation and local delivery of chlorhexidine directly on to the microbial cell membrane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 36 publications
0
40
0
Order By: Relevance
“…The viability decreases further after six hours and, after one day, it resulted in approximately 97% loss of viability. Past research suggested that the antibacterial effect might be credited to multiple factors: (i) the cellular internalization of NPs where they could potentially interfere with the bacterial DNA and cellular organelles [41,42,43,44,45]; (ii) immediate contacts with the bacterial cell wall [23,24]; and, (iii) the increased local dissolution of metal ions of the nanoscale metal oxide [46,47]. Usually, the antimicrobial impact is dependent on the size of the nanoparticles and a better antimicrobial effect is achieved with smaller nanoparticles [17,48,49,50].…”
Section: Resultsmentioning
confidence: 99%
“…The viability decreases further after six hours and, after one day, it resulted in approximately 97% loss of viability. Past research suggested that the antibacterial effect might be credited to multiple factors: (i) the cellular internalization of NPs where they could potentially interfere with the bacterial DNA and cellular organelles [41,42,43,44,45]; (ii) immediate contacts with the bacterial cell wall [23,24]; and, (iii) the increased local dissolution of metal ions of the nanoscale metal oxide [46,47]. Usually, the antimicrobial impact is dependent on the size of the nanoparticles and a better antimicrobial effect is achieved with smaller nanoparticles [17,48,49,50].…”
Section: Resultsmentioning
confidence: 99%
“…Finally, samples were dried at critical point using liquid carbon dioxide. 41,42 The microorganisms before and aer treatment with the CuONPs (bare and HPBA-graed) were imaged using a SEM. Aer incubation with CuONPs, the cells were studied with TEM via the following procedure.…”
Section: Methodsmentioning
confidence: 99%
“…[20][21][22][23][24]45 AgNPs has been researched in anti-biofilm treatments due to the silver ions intrinsic antimicrobial property. 25,43 Nanocarriers for antimicrobial agents have also been shown to increase their efficacy against a wide range of microorganisms, including resistant species [26][27][28][29] and deliver drugs specifically to a bacterial target. 35,[42][43][44] This can potentially reduce unwanted drug interaction in healthy tissue and lower general toxicity.…”
Section: Introductionmentioning
confidence: 99%